2015
DOI: 10.1139/cjp-2014-0631
|View full text |Cite
|
Sign up to set email alerts
|

On the connection between the theorems of Gleason and of Kochen and Specker

Abstract: We present an elementary proof of a reduced version of Gleason's theorem and the Kochen-Specker theorem to provide a novel perspective on the relation between both theorems. The proof is based on a set of linear equations for the values of a function m on the unit sphere. In the case of Gleason's theorem the entire unit sphere needs to be considered, while a finite set of points suffices to prove the Kochen-Specker theorem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The original KS theorem holds for vectors and defines a KS set as its constructive proof. On the other hand, Bell proved the so-called Bell theorem [75] as a corollary to the Gleason theorem [76] which is a projector formulation of the KS theorem [73,77]. Theorem 3.3.…”
Section: Theorem 32 Ks Mmp Hypergraphsmentioning
confidence: 99%
“…The original KS theorem holds for vectors and defines a KS set as its constructive proof. On the other hand, Bell proved the so-called Bell theorem [75] as a corollary to the Gleason theorem [76] which is a projector formulation of the KS theorem [73,77]. Theorem 3.3.…”
Section: Theorem 32 Ks Mmp Hypergraphsmentioning
confidence: 99%
“…The original KS theorem holds for vectors and defines a KS set as its constructive proof. On the other hand, Bell proved the so-called Bell theorem [71] as a corollary to the Gleason theorem [72] which is a projector formulation of the KS theorem [69,73].…”
Section: Extensions Of the Kochen-specker Theoremmentioning
confidence: 99%
“…Gleason theorem had a major influence on Specker. It was actually shown that the Kochen-Specker theorem could be seen as a consequence of Gleason's: it constructs a finite set of rays on which no two-valued homomorphism exists, the existence of which is established by a simple extension to Gleason's theorem [93,94].…”
Section: The Gleason Theorem and Quantum Mechanics As A Prevision The...mentioning
confidence: 99%